2010
DOI: 10.1007/s00405-010-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rhinosinusitis among atypical cystic fibrosis patients

Abstract: The objective of this paper is to study the correlation between sinonasal involvement and type of cystic fibrosis (CF) in Israeli's CF patients. The comparative study includes 70 CF patients: 40 typical and 30 atypical CF patients. History and physical examination data were recorded, including endoscopic nasal examination as well as sinus computer tomography scan. The data collected from the two groups were statistically analyzed. Twenty-seven percent of atypical CF patients compared with 2.5% of typical CF pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Unlike in other studies, Marshak et al . found that symptoms related to asthma or sinonasal involvement were significantly more common in atypical CF patients than in typical CF patients.…”
Section: Resultsmentioning
confidence: 64%
“…Unlike in other studies, Marshak et al . found that symptoms related to asthma or sinonasal involvement were significantly more common in atypical CF patients than in typical CF patients.…”
Section: Resultsmentioning
confidence: 64%
“…Marshak et al found that chronic rhinosinusitis and nasal polyps were common in patients with CFTR‐related disease. The frequency of severe chronic rhinosinusitis was also somewhat higher in those with CFTR‐related disease than classical CF, but statistical significance was not attained …”
Section: Discussionmentioning
confidence: 92%
“…CRS is reported in 30 to 67% of patients with CF (within all age groups) [116][117][118][119]. Some studies have suggested that this may be because of genetic mutation, such as the ∆F508 and 394delTT mutation in Finland [120].…”
Section: Cystic Fibrosis (Cf)mentioning
confidence: 99%